(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now a days India to facing problem of water shortage hence it is necessary to find the other ways to achieve water. Atmospheric water generation (AWG) is the one of the process which is under experimentation by the scientist around the world. In this dissertation report AWG is developed based on Vapor Compression cycle (VCC). Efforts are put on condensation of maximum moisture in air by enhancing the performance of VCC by employing subcooling using water cooled condenser. And it is observed that it is possible to produce large amount of water if system is enlarged by size. Though the system running cost is higher but its side product like cooled air and hot water from the condenser indirectly saves the energy consumption to cool the air and heat the water for different purposes. Average range of 700 to 1600 ml of water generated running the system for 14 hours per day during December 2016 and January 2017. Subcooling improves the water generation indirectly by increasing the performance of VCC. Simulation is done for the system with subcooling and without subcooling and the results shows that COP of the subcooled system is 12-14% more than without subcooled system. A system without subcooling collected only average 700 ml of water per day. This shows that practically subcooled system is average 50% efficient as far as water condensation is concern. The air velocity of the fresh air entering in the evaporator also plays the vital role in deciding the amount of water condensation from air, it is found that at 4-6 m/sec of air velocity maximum water collection is take place.